Engaging Distance Learners in Cooperative Extension - Austen Moore; Amy Harder (EDIS)
Distance education allows organizations to reach broader audiences, reduce costs per learner, and better serve communities. This 4-page fact sheet discusses how to incorporate the best practices for engaging learners in online distance education programs. Written by Austen Moore and Amy Harder, and published by the UF Department of Agricultural Education and Communication, May 2013.